Advances in the use of nanocarriers for cancer diagnosis and treatment - Vieira,Débora Braga (2016)
ABSTRACT The use of nanocarriers as drug delivery systems for therapeutic or imaging agents can improve the pharmacological properties of commonly used compounds in cancer diagnosis and treatment. Advances in the surface engineering of nanoparticles to accommodate targeting ligands turned nanocarriers attractive candidates for future work involving targeted drug delivery. Although not targeted, several nanocarriers have been approved for clinical use and they are currently used to treat and/or diagnosis various types of cancers. Furthermore, there are several formulations, which are now in various stages of clinical trials. This review examined some approved formulations and discussed the advantages of using nanocarriers in cancer therapy.